Implementing The Kirkpatrick Model in Job Training Management: A Qualitative Case Study at BBPVP Semarang - Imelia Sahda Salsabilla; Nur Asiyah; Syaiful Bakhri; Zarkasi Zarkasi; Gamal Abdul Nasir Zakaria (Jurnal Pendidikan Vokasi, 2026)
Although the Kirkpatrick model has been widely adopted to evaluate training effectiveness, its application has predominantly focused on post-training assessment rather than its strategic integration into planning, implementation, evaluation, and continuous improvement throughout the training management cycle. This study aimed to examine how the Kirkpatrick model functions as an integrated job training management framework for enhancing workforce readiness and organizational productivity at the Semarang Vocational Development and Productivity Center (BBPVP). A qualitative case study design was employed involving nine purposively selected participants. Data were collected through in-depth interviews, observations, and document analysis and analyzed using the Miles and Huberman interactive model with source triangulation to ensure credibility. The findings indicate that systematic industry-based planning, competency-based instructional implementation, and integrated multi-level evaluation collectively strengthened participant competencies, workplace readiness, and organizational productivity. However, several challenges remained, including variations in instructional quality, limited training facilities, fragmented evaluation systems, and insufficient post-training monitoring. The findings further reveal that the four Kirkpatrick levels function as interconnected managerial feedback mechanisms linking planning, instructional implementation, behavioral transfer, organizational outcomes, and continuous program improvement. This study reconceptualizes the Kirkpatrick model as an integrated vocational training management framework rather than merely a post-training evaluation model, thereby extending its theoretical application in Technical and Vocational Education and Training (TVET) and workforce development.